Grabież mienia w świetle prawa – działalność Feliksa Blümela z antykwariatu „Caesar Mann” w Poznaniu w latach 1939–1943 - Syska, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
Before 1939, there were about 10 antique shops in Poznań offering works of art and antiques, one of which, Caesar Mann, was owned by the Germans Erika and Feliks Blümels. In late 1939 and early 1940, this antique shop played a key role in the shutdown of Polish antiques trade in Poznań through raids and takeover of Polish stores. Those activities were legitimised by Izba Przemysłowo-Handlowa (the Chamber of industry and trade) in Poznań, which appointed Feliks Blümel as the trustee (German: Treuhänder) of Poznań’s antique stores. The Caesar Mann company stole works of art in Poznań with the approval of the local museum (Kaiser Friedrich Museum Posen) and university (Reichsuniversität Posen) communities. In October 1942, Blümel moved his business to Łódź and worked there with German customers, moving items, among others, to the benefit of the Führermuseum in Linz. After the war, he settled in Munich, where he continued to work in the antiques trade.